2009
DOI: 10.1016/j.virol.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Products and substrate/template usage of vaccinia virus DNA primase

Abstract: Vaccinia virus encodes a 90-kDa protein, conserved in all poxviruses, with DNA primase and nucleoside triphosphatase activities. DNA primase products, synthesized with a single stranded ϕX174 DNA template, were resolved as dinucleotides and long RNAs on denaturing polyacrylamide and agarose gels. Following phosphatase treatment, the dinucleotides GpC and ApC in a 4:1 ratio were identified by nearest neighbor analysis in which 32P was transferred from [α-32P]CTP to initiating purine nucleotides. Differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Nevertheless, the observed length distributions suggest that the fragments are considerably shorter than the ∼1-kb long fragments that have been reported previously (10); however, there was no data on the presence of RNA primers in those long fragments. Previous in vitro studies had shown a preference for the VACV primase to start at a purine followed by a pyrimidine (37). In the present study, some sequence specificity was found at the junction between the RNA primer and the DNA moiety in nascent VACV fragments.…”
Section: Consensus Nucleotides At the Start And End Of Vacv Dna Fragmsupporting
confidence: 63%
“…Nevertheless, the observed length distributions suggest that the fragments are considerably shorter than the ∼1-kb long fragments that have been reported previously (10); however, there was no data on the presence of RNA primers in those long fragments. Previous in vitro studies had shown a preference for the VACV primase to start at a purine followed by a pyrimidine (37). In the present study, some sequence specificity was found at the junction between the RNA primer and the DNA moiety in nascent VACV fragments.…”
Section: Consensus Nucleotides At the Start And End Of Vacv Dna Fragmsupporting
confidence: 63%
“…To determine whether B1 is unique in functioning at both of these stages of the viral lifecycle, we examined whether intermediate gene expression was decreased during infection with other ts viruses displaying blocks in DNA replication. Specifically, two ts mutants with DNA replication defects were employed: ts42 virus carries a mutation in the viral catalytic DNA polymerase (E9) (McDonald and Traktman, 1994, Sridhar P and Condit, R.C., 1983) and ts24 carries a mutation in the D5 primase/helicase protein (De Silva et al, 2007, De Silva et al, 2009, Evans, 1992, Evans et al, 1995). First, we verified that viral DNA replication was impaired at 37°C during infection with these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Most insertions were found to contain multiple repeats, consistent with the fact that at least two repeats are required for the strand slippage to occur, and therefore the resulting sequence will contain three repeats, or more, if the event has occurred multiple times. The fact that the generation of indels via strand slippage tends to occur during lagging-strand synthesis [25] is interesting because although the mechanism by which the poxvirus is replicated is unclear [26], with the recent discovery of a poxvirus primase activity [27] and the prediction of a flap-like nuclease [28] there is mounting support for a leading-lagging strand synthesis mechanism. Additional information about the frequency of indel generation during replication might be gleaned thorough reviews of data sets from Next Generation Sequencing runs.…”
Section: Discussionmentioning
confidence: 99%